David Hume's political essays - Hume,David; Hendel,Charles W. (ed.) (New York, 1953)
In My Own Life, one of the briefest of autobiographies, told in less than eight pages, David Hume speaks of his Political Discourses (1752) as "the only work of mine that was successful on the first publication. It was well received abroad and at home." That book was second volume of Essays Moral and Political, the first of which had appeared ten years earlier in 1742, at which time also Hume says, "the work was favorably received and soon made me entirely forget my former disappointment. The "disappointment had been over his first philosophical work, a large book in three volumes
Keywords: Political and government